Analysing The Intricacies Of Modern Relationships And Social Identity Dynamics In Sally Rooney's Novel 'Normal People' (2018) (Journal of Namibian Studies : History Politics Culture, 2023)
This research delves into the intricate examination of modern relationships and social identity in Sally Rooney's novel 'Normal People' (2018). This critical study aims to explore the obstacles faced by Connell and Marianne as they negotiate societal norms and undergo personal development. The primary objective of this study is to examine the complex dynamics that exist within modern relationships, taking into account a range of aspects such as socioeconomic status, communication patterns, and individual backgrounds. In order to get a deeper understanding of relationship dynamics in the actual world, this study investigates the socio-psychological factors that impact the relationships between individuals. The significance of this research lies in its ability to provide light on the complex dynamics between intimacy and social identity within the context of the digital era. One approach to qualitative research is using literary analysis and sociocultural frameworks to analyse the motivations and experiences of characters in order to accomplish certain objectives. The approach is grounded on the theoretical framework of George Herbert Mead's symbolic interactionism. This theoretical framework elucidates the manner in which the primary subjects of the research construct their identities via engagements within social contexts. This research demonstrates the adept portrayal of intricate dynamics in contemporary relationships in the novel 'Normal People', highlighting the need for open and empathetic dialogues among the many obstacles encountered within society.